SI PADOR (Sistem Penyewaan Alat Outdor) Sebagai Media Sewa Alat Outdor Berbasis Website Studi Kasus CV Pondok Pendaki - Yoki Firmansyah; Reza Maulana; Wahyu Anggara (LPPM Universitas Bina Sarana Informatika, 2020)
CV. Pondok Climber is a company engaged in the rental of outdoor equipment and tour guide services. Based on the results of analysis and observations made on the CV. Pontianak Climber Hut, booking goods rental only uses social media as a means of ordering goods rental, this will certainly take a long time in serving goods rental bookings made by consumers. Seeing these problems, in this study, we created a web-based outdoor goods rental information system using a prototype model to solve the problems that occur. the company to explain the details of goods to be rented. Consumers can order goods in accordance with the desires needed by consumers. The design of this system is expected to improve the performance of CV. Pontianak Climber Cottage in managing data rental of goods from consumers.